Educação infantil na rede municipal de ensino de Uberlândia/MG: uma investigação sobre o currículo e os diários de classe - Silva, Cecilia Rezende (2019)
This research had as object of study the curriculum of early childhood education, children from up to five years old, in the public schools of Uberlandia, MG city, to investigate the relationship between what was prescribed in the official documents and the constants records in the class diaries. The objectives of this research were: to identify if the normative documents were recognized in the filling of the class diaries; if there were dissonances or if the pedagogical practices registered were in agreement with what it was recommended in the official documents and to ascertain the evaluative aspects, as well as to know if the diverse cultures present in the school context were contemplated. In addition, we search to verify evidence of the early schooling process, in other words, it is the anticipation of knowledge that should be constructed throughout elementary school. This investigation was structured in a Documentary Research characterized by the procedures of reading and analysis of official documents that deal with the education of children (Law of Directives and Bases of National Education 9394/96, National Curriculum Standards for Early Childhood Education (1998), Curricular Directives - Municipal Early Childhood Education (2003), Daily practices in early childhood education: bases for reflection on curricular guidelines), Resolution No. 5 of the National Education Council (2009), National Curricular Directives for Early Childhood Education (2010), National Education Plan (2014), Normative Instructions of the municipal government of Uberlandia / MG n ° 12 of 2016 at 06 2017 and others); study of academic papers (articles, theses and dissertations searching for the keywords child education, curriculum, records, early schooling); content analysis of 220 class diaries from the years 2016 and 2017, municipal schools of early childhood education and civil society organizations subsidized by the city hall. The analysis of the class diaries happened in five moments: 1- general reading of the whole set of documents; 2 - deepening the analysis to understand of the important issues; 3- analysis of content and categorization of records; 4- consolidation of the results of the previously performed analyzes highlighting day care center and pre-school; 5- Highlights of pre-school, children from four to five years old, (reception, play, routines, discipline and writing). Identify the prevalence of play activities; prevailing fixed routines; themes that should be cross-cutting and were worked exclusively on commemorative dates; absence of certain practices prescribed in official documents; emphasis on the mechanical tasks of writing (pre-school classes); scarcity of evaluation records; incomplete descriptions; identical records regardless of their curricular component. These results have been indicated that the class diaries have been filled in a particular way and in a lacunar manner, and it makes us wonder about the reasons that could explain this situation. Therefore, we understand that maybe it has been happened because of the lack of time at work, lack of adequate technical resources and skills to deal with the virtual dimension, the class diaries that we analyzed, did not report much about the connections between the prescribed and the accomplished in the education of children and also they did not present themselves as part of an important practice of planning and evaluation of the educational work. In this sense, the diaries analyzed have been shown more like a bureaucratic activity, without unfolding for the educational work and for the continued formation of teachers, indicating the existence of the process of early schooling, especially those related to literacy and numbering.